An efficient approach to the synthesis of hydrazinyl pseudo-peptides - Fathi, Vaezeh; Rominger, Frank (Helvetica chimica acta, 2014)
New hydrazinyl pseudo-peptides have been obtained from Ugi four-component reaction (4CR). The 5-hydrazinyl-5-oxopentanoic acids used as starting materials were prepared by the reaction of hydrazides with anhydrides. Mild reaction conditions, high atom economy, bond-forming efficiency, and easy workup are advantages of this approach. The products have four amide bonds and high potential for H-bonding.
Gesehen am 16.10.2020